Pharmacogenetic risk factors for altered bone mineral density and body composition in pediatric acute lymphoblastic leukemia - te Winkel, Mariël L. (Ferrata Storti Foundation, 2010)
BACKGROUND: This study investigates pharmacogenetic risk factors for bone mineral (apparent) density (BM(A)D) and body composition in pediatric acute lymphoblastic leukemia DESIGN AND METHODS: We determined the influence of SNPs in 4 genes (vitamin-D receptor (VDR: BsmI/ApaI/TaqI and Cdx-2/GATA), collagen type I alpha 1 (SpI), estrogen receptor 1 (ESR1: PvuII/XbaI), glucocorticoid receptor (BclI)) on body composition, BM(A)D and fracture risk during dexamethasone-based pediatric acute lymphoblastic leukemia treatment. Body composition and BMD were measured repeatedly during and after treatment using dual energy X-ray absorptiometry. RESULTS: Non-carriers of VDR 5′-end (Cdx-2/GATA) haplotype 3 revealed a significant larger fat gain than carriers (Δ%fat: non-carriers: +1.76SDS, carriers: +0.77SDS, P<0.001). At diagnosis and during therapy, lumbar spine BMD was significantly higher in non-carriers of VDR 5′-end (Cdx-2/GATA) haplotype 3 than in carriers. The other SNPs did not influence BMD or fracture risk during/after treatment. The year after treatment completion, lean body mass increased in non-carriers of ESR1 (PvuII/XbaI) haplotype 3 and decreased in carriers (Δ lean body mass: non-car-riers:+0.28SDS, carriers: −0.55SDS, P<0.01). CONCLUSIONS: Only VDR 5′-end (Cdx-2/GATA) haplotype 3 was identified as protective factor against excessive fat gain and as a risk factor for lower lumbar spine BMD during treatment. Carrying ESR1 (PvuII/XbaI) haplotype 3 negatively influenced recovery of lean body mass after pediatric acute lymphoblastic leukemia treatment.